Development Trend of Agricultural Brand E-commerce Mode from the Perspective of New Media. Issue 4 (August 2021) - Liu, Shihai; Gao, Ziyuan; Zhu, Xialing
Abstract: With the deepening of reform and opening up, China's economic construction level has been greatly improved, and the progress of social economy has enhanced consumers' brand awareness to a certain extent. This paper mainly studies the development trend of agricultural product brand e-commerce model from the perspective of new media. This paper expounds the agricultural product brand design in new media environment elements and principles to follow, with new media, the characteristics, properties, methods, such as theoretical knowledge as the foundation, through the spread of new media commonly used methods for analysis, and combining the domestic and international excellent brand promotion, brand image design of agricultural products in the new media to make certain guidance and explored.